Meditations on the Ideology of Inquiry in Higher Education Research - Conrad, Clifton (My University, 2007)
In his presidential address to the Association for the Study of Higher Education (ASHE) two decades ago, Professor Conrad challenged the conventional beliefs that guide higher education research. In this brown bag forum, he will revisit his argument in light of contemporary higher education research and invite participants to engage in an irreverent critique of the topic.
Keywords: History and Philosophy